PSYCHOLINGUISTICS AND ITS CONNECTION WITH SPEECH" (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In the study of the value of a work of art and its scope, special attention is paid to the knowledge of the act of speech and its impact on the person, ie the character within the work. we have partially touched on the issues of psycholinguistics.